LITERACY ASSESSMENT IN MULTILINGUAL CONTEXTS: A REVIEW OF CURRENT APPROACHES - Puspita Dian Agustin; Abdul Wahab Syakhrani (INJOSEDU: International Journal of Social and Education, 2025)
The assessment of literacy skills in multilingual contexts has become an important focus in the era of globalisation, where individuals increasingly interact in multiple languages. Multilingual literacy not only includes reading and writing skills, but also involves understanding culture and linguistic context. This paper reviews current approaches to multilingual literacy assessment, including the integration of computer-based technology and personalisation of assessment based on individual experience. Technology-based approaches allow for more in-depth analysis through big data and adaptation to participants' language abilities, while personalised approaches consider social, economic and educational factors. While these assessment approaches bring many benefits, they also face challenges in ensuring equity and inclusion for participants from different language backgrounds. This review emphasises the importance of using current approaches to support the development of more inclusive education policies to improve the literacy skills of multilingual communities globally.